(3GdJTha Edi QLGd GdJUhas - (3jhSa Hf jMji Hf YjSi Hf YHO GdQMef GdJGOdj, CHh GdMLGL, GdeYQha HGHf GdnqRnqjGJ,J (B627 (3g` s ((3CHh GdYHGS CMeO (B( (3MejOI (B) (3Hf CHj GdMSf Ydi s)
(3ChdgG (B:s
(3GdMeO ddg GdYdi CeG HYO , aEfg de jNd ReGf ef hdi ef ChdjGA Gddg JYGdi jMaX Gddg Hg GdHdGO hjQMe Hg GdYHGO hSejJ gPG GdcJGH HGdJTha Edi QLGd GdJUha , hEf cGf eTJedkG Ydi CVQGH ef CaGVd GdYdeGA hGdabgGA s
(3BNQgG (B:s
(3bGd Gdabjg CHh jYbhH jhSa Hf jMji Hf YjSi bO CJjJ HMhd Gddg JYGdi PcQ YHGO Gddg haO CPfJ ajg def hba ajg Ydi hge Ch ZdW Cf jUdMg Je GdcJGH HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3CJe JCdjag SfI (B618 (3g` hLYdg Ydi ebOeI hSHYI CHhGH hai JQGLe GdChdjGAs
(3HChdgG agQS dCHhGH GdcJGH hGdeJQLejf SfYg GdWGgQ Hf GdeMLhH SfI (B1314 (3g`s
(3HChdgG JQLeI ddeDda ai GdeYgO fSNI CNQi HQbe (B1503 (3JGQjN hajg NdGa ai YfhGfg heDdag hdY s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdJGQjNs